NILAI-NILAI PENDIDIKAN ISLAM DALAM UPACARA HAJAT SASIH PADA MASYARAKAT KAMPUNG NAGA TASIKMALAYA - Jajang Sukandar (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam YAPTIP Chadijah Ismail Pasaman Barat, 2020)
This research is motivated by the fact that in Indonesia lately it is quitealarming. The reality is that now the Indonesian nation has lost its nationalidentity with a number of cases of violence, anarchist acts, corruption, taxevasion, murder, sexual crimes, looting, bomb terror, fights and others. Forthis reason, the role of education is very much needed to filter out thesecultures so that the community is not carried away by globalization, especiallyin terms of culture, but can analyze what cultures are acceptable and inaccordance with existing norms. The purpose of this study is focused on:culture Kampung Naga, the procession of love, the values contained in love,the internalization of educational values and the cultural implications ofIslamic education towards the social life of the people of Kampung Naga. Thisresearch uses a qualitative approach, with descriptive analytic methods. Thelocus of this research is the traditional village of Naga Tasikmalaya. The datacollection techniques are interview, observation and documentation. While theanalysis of the data is through data reduction, data display, and drawingconclusions.The results showed that: by applying the values of Islamiceducation in the Hajat Sasih ceremony to the people of Kampung NagaTasikmalaya, it was hoped that the formation of human characters throughhabituation of these values both in the family, school and community.